2001
DOI: 10.1007/s11663-001-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous interfacial heat fluxes during the 4 to 8 m/min casting of carbon steels in a twin-roll caster

Abstract: Instantaneous heat fluxes between the roll and the solidifying metal were evaluated in a pilot twinroll caster, producing strips of low-carbon steels. This evaluation was based on the solution of an inverse heat-transfer problem, using temperature readings of thermocouples inserted at various locations in the roll sleeve. The response times of the thermocouples were determined and used to correct measured temperatures. The variation of the instantaneous heat fluxes with time of contact between the roll and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…And the relationship between the curve shape and the rolling speed obtained in the simulation results partly confirmed the previous work of Tavares et al 10) in the TRC process.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…And the relationship between the curve shape and the rolling speed obtained in the simulation results partly confirmed the previous work of Tavares et al 10) in the TRC process.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the previous work of Tavares et al, 10) the second peak of the heat flux was observed in the simulation results, lower and wider than the first peak. According to the schematic of the TSTRC process, the second peak can be ascribed to the rolling pressure, corresponding to the location of solidification end close to the roll nip.…”
Section: (9)supporting
confidence: 91%
See 2 more Smart Citations
“…Tavares et al (2001) [3] proposed an inverse method based on one-dimensional model (Lagrangian coordinate system moving at the same speed as the roll). The response time of the thermocouple is studied and a proper correction of the temperature data is introduced.…”
Section: Introductionmentioning
confidence: 99%